Efficacy of Streptomyces Formulation for the Induction of Defense Response in Rice Challenged with Bacterial Leaf Blight Pathogen Xanthomonas oryzae pv. oryzae - Jaivel, N.; Partheeban, C.; Kasinathan, S.; Rajesh, R. (International Journal of Economic Plants, 2025)
The present study was conducted during the kharif season (June–September, 2019) at the Department of Agricultural Microbiology, Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu, India (11.01°N, 76.93°E) to evaluate the efficacy of a Streptomyces-based formulation in managing bacterial leaf blight (BLB) of rice. Biological control has been gaining increasing importance in recent years for the management of plant diseases. A water-soluble starch-based formulation was developed using dried spores and mycelia of Streptomyces sp. TC1, a strain exhibiting inhibitory activity against Xanthomonas oryzae pv. oryzae, the causal organism of BLB. The TC1 formulation effectively reduced seed-borne infection and enhanced the germination percentage of paddy seeds by 78.7%. Foliar application of the formulation at varying concentrations significantly induced systemic resistance in rice plants, as evidenced by increased activity of defense-related enzymes such as peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL), superoxide dismutase (SOD), and elevated total phenol content. Among the tested concentrations, the 0.4% TC1 formulation was identified as optimal, resulting in a 56.6% reduction in disease incidence under pot culture conditions compared to the untreated control. Furthermore, application of the TC1 formulation up to 1% concentration did not exhibit any phytotoxic effects on rice plants. The findings suggest that the TC1 formulation could serve as a promising biocontrol agent for the eco-friendly and sustainable management of bacterial leaf blight in rice cultivation.